Seed production of pasture species in a tropical savanna region of Brazil. 2. Grasses - Andrade, Ronaldo P. de; Thomas, D.; Ferguson, John E. (1983)
The seed yields and limitations to seed production for four tropical grass cultivars were defined via a replicated field experiment conducted over three years at the Cerrados Agricultural Research Centre near Brasilia (latitude 15° 36' S; longitude 47° 42' W) in a tropical savanna region. The four grasses were Brachiaria humidicola, B. decumbens cv. Basilisk, Panicum maximum var. trichoglume cv. Petrie and Andropogon gayanus var. bisquamulatus cv. Planaltina. The highest pure seed yields obtained ranged from 330 kg ha 1 for A. gayanus cv. Planaltina, to 501 kg ha 1 for B. humidicola. Observations on flowering behaviour suggested that both Brachiaria species and P. maximum cv. Petrie were day-neutral in their photoperiodic responses. A. gayanus cv. Planaltina had a short-day flowering response. Yields were not limited by diseases or weeds. Under the relatively high soil fertility conditions, undefoliated stands of A. gayanus cv. Planaltina lodged badly in the second season and seed yield was reduced by 65 per cent. In the following year, however, cutting in January prevented lodging and significantly increased seed yield. Results indicated that the region is potentially suitable for seed production of all the grasses studied.